Does perceived organizational support matter? The effect of high-commitment performance management on supervisors’ performance - Rubel, Mohammad Rabiul Basher; Kee, Daisy Mui Hung; Daghriri, Yahya Qasim; Rimi, Nadia Newaz (Frontiers in Psychology, 2023)
The current research aims to investigate the connection between supervisors' perceived high commitment performance management (HCPM) and their performances (in-role, extra-role, and deviant work behavior). In addition, this paper aims to examine how perceived organizational support (POS) mediates the above relationship. The paper employs the social exchange theory as the theoretical lens to develop and suggest a positive motivational work environmental model. Our model is tested on a sample of 430 supervisors from ready-made garment (RMG) organizations, Bangladesh. Using the PLS-SEM, our model examines the direct and indirect effects of HCPM and POS on job performances. We find supports for the existence of a positive relationship from HCPM to job performance through POS mediating such a relationship. Future studies may investigate the prospective of HCPM and POS to create ideal work environments that boost employee productivity and benefit enterprises.